2008
DOI: 10.1177/1534484308324521
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Literature Review: Methods in Identifying Exemplary Performance: A Review of the Literature and Implications for HRD

Abstract: This literature review provides an analysis of relevant ASTD (American Society for Training & Development) competency studies in Workplace Learning and Performance (WLP) and other research findings related to the methodology used in identifying exemplary and average performers.These findings helped create the research model and methods used in the qualitative data collection for the rubric used for the CPLP (Certified Professional in Learning and Performance) pilot exam. This chronicle is for those who seek ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…HRDQ included articles on workplace practice and informal learning (Doornbos, Simons, & Denessen, 2008), developing expertise in strategic thinking (Goldman, 2008), and an instrument for human capital planning. HRDR articles presented the integrated model of expertise development (Grenier & Kehrhahn, 2008) and methods to identify exemplary performance (Smith, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HRDQ included articles on workplace practice and informal learning (Doornbos, Simons, & Denessen, 2008), developing expertise in strategic thinking (Goldman, 2008), and an instrument for human capital planning. HRDR articles presented the integrated model of expertise development (Grenier & Kehrhahn, 2008) and methods to identify exemplary performance (Smith, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…He advocated technology-delivered instruction to meet the challenge of rapidly obsolescent knowledge as well as training for learning and relearning. In a literature review, Smith (2008) found workplace learning studies and foundational expertise most relevant in identifying methods to differentiate between average and exemplary performers and the lack of measureable indicators and outputs a limitation in developing a model for exemplar status.…”
Section: Resultsmentioning
confidence: 99%
“…In regards to the data collected through two qualitative instrument. Those two instrument were observation and unstructured interview (Smith, 2008;Parsons, 2012;Mukhopadhyay & Gupta, 2014). Observation was done among college student from fourth private universities and an institute in Malang city.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, competencies include abilities associated with a specific job performance and a set of personal characteristics including knowledge, skills, attitudes, traits, values, motives, self-concept and beliefs (Mclagan, 1989; Spencer and Spencer, 1993). They demonstrate the way in which people behave, think or generalize across situations (Smith, 2008).…”
Section: Review Of Literaturementioning
confidence: 99%